Context-dependent memory in the real world: the role of frequency and context dwell time - Choi, Yura; Kim, Kawon; Moon, Sunwoo; Jung, Geunseong; Cha, Jae-Hyuk; Yim, Hyungwook (Frontiers in Psychology, 2025)
We investigated the context-dependent memory effect outside of the laboratory in order to examine whether the effect impacts everyday memory retrieval. We also examined various factors that may interact with the context-dependent memory effect such as frequency and context dwell time. In the experiment, we used a smartphone app to track participant’s GPS locations for 5 weeks. Participants, during their daily lives, were then asked to recall their locations at a specific date and time by choosing from all locations visited in the previous 5 weeks. Results demonstrated the existence of the context-dependent memory effect in a real-world setting, with low-frequency locations showing a stronger context-dependent memory effect—benefiting more from the matched context. We also found that for low-frequency locations, the benefit of the context-dependent memory effect increased as the participant spent more time in the context (context dwelling time). The study provides a novel way to examine the context-dependent memory effect outside of the laboratory, which not only enables researchers to measure an individual’s genuine memories in a more ecologically valid way, but also investigates factors that would be challenging to examine in the laboratory.